2011
DOI: 10.1111/j.1399-0004.2010.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential amelioration of morbidity in patients with chromosomal anomalies: relevance to Bardet-Biedl syndrome

Abstract: Given the genetic basis of their disease, children with major chromosomal abnormalities including Bardet-Biedl syndrome (BBS) are generally considered to have a guarded prognosis with persistence or progression of disease manifestations. Although various therapeutic interventions are commonly used to control signs and symptoms of illness, parents of BBS children are usually cautioned against hoping for sustained improvement. A case of a 21-month-old girl, diagnosed with BBS, manifesting signs of worsening visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Astonishingly, this child experienced a remarkable improvement of vision, resolution of obesity, normalization of behavior and mood, and restoration of normal development during the following 2 years and remained virtually healthy by the time of publication, i.e. being 7 years old [Genuis and Lobo, 2011]. While already established organ anomalies are notoriously difficult to treat, the mere delaying of BBS symptoms, if started from birth, may eventually turn out to be a feasible strategy.…”
Section: Involved In Intraflagellar Transportmentioning
confidence: 93%
See 2 more Smart Citations
“…Astonishingly, this child experienced a remarkable improvement of vision, resolution of obesity, normalization of behavior and mood, and restoration of normal development during the following 2 years and remained virtually healthy by the time of publication, i.e. being 7 years old [Genuis and Lobo, 2011]. While already established organ anomalies are notoriously difficult to treat, the mere delaying of BBS symptoms, if started from birth, may eventually turn out to be a feasible strategy.…”
Section: Involved In Intraflagellar Transportmentioning
confidence: 93%
“…Other approaches, e.g. as in the above-mentioned case based on nutritional correction [Genuis and Lobo, 2011], deserve rapid clinical assessment. In addition, population-based genetic screening is gradually becoming more achievable, thanks to decreasing costs and improving throughput for DNA-based assays.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting case report suggesting that metabolic factors may contribute to organ dysfunction in BBS was published in 2011 [58]. The authors reported the case of a 21-month-old girl, with polydactyly at the birth and obesity during the first infancy.…”
Section: Evidence Supporting the Role Of Systemic Factors In Kidney Dmentioning
confidence: 99%
“…Preventing birth defects by securing adequate folic acid [57], relieving post-partum depression by correcting fatty acid deficiency [40], restoring mental health by eliminating stockpiled toxicants [5860], reversing some cases of autism by removing incitants and addressing nutritional deficiencies [22, 61], treating pediatric arthritis by managing food intolerances [62], overcoming impairment resulting from some chromosomal anomalies by remediating biochemistry [63], resolving inflammatory bowel disease with avoidance of sensitivities [53], relieving asthma and chronic fatigue by mold remediation [48], ending the tragedy of habitual abortion by addressing electromagnetic toxicity [50], and the author's experience of achieving remission from leukemia in a patient by eradicating retained aflatoxin are all examples of what can possibly be realized if underlying causes of sickness are explored, identified, and properly managed. …”
Section: Quo Vadis: Science-based Medicinementioning
confidence: 99%